PERBAIKAN MANAJEMEN DAN PENGEMBANGANDESAIN PRODUK KERAJINAN UKIR BATU UNTUKMENINGKATKAN PASAR EKSPOR DAN PASAR DOMESTIK - dan Ismanto, Yuni Pratiwi (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
Gunungkidul as mountain area of chalk have the availibility of whitestone raw material very abundance. This condition push society creativity to developwhite stone become carve product valuable stone economics and have sellvalue highly. Carve stone product of Gunungkidul in this time have been marketedin country and abroad. Some constraint in developing the effort whitestone the limited production appliance, quality of product is optimal yet, andmanagement which still is traditional, so that development walk slowgoingly. Todevelop effort carve white stone Gunungkidul need development of desain, repairof management especially in accuracy of solving of order, ability to fulfillamount ordered, fix of bookkeeping administration and making of financial statement.Other important matter to develop market export and domestic market.Some activity to develop the effort of white stone Gunungkidul covermaking of cutter machine - square, making of jacking appliance - conveyor,training of product quality and desain. Cutter machine - square, can quickencompletion task of cut the stone materials carve with quality of result betterform and cutting. Result of cutting by manual previously can only yield fivecutting/ hour, mechanically cutter - square can yield thirtieth cut / hour. Jackingmachine - conveyor can improve capacitiy lifting of materials, a quarter semitruck / day become four truck / day. Repair of management with training of productionmanagement, training of goods exporting, training of compilation ofFinancial statement and bookkeeping of company. To reach market which isbroader, it will be marketing by WEB so that the small enterprise can communicatewith its market directly.